Pengembangan Sistem Pembelajaran Bahasa Inggris Menggunakan Pendekatan Gamifikasi - Ilham Pambudi; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
English has been an international language for communication among global citizens. A good English ability is highly required for Indonesians to be able to communicate with other people around the world. However, learners in Indonesia frequently encounter a myriad of challenges in learning English, including their reluctance to study new English vocabulary, worry of making mistakes, and feeling bored with the conventional teaching methods. The main four English skills that should be mastered by the learners are writing, reading, listening, and speaking. Excellent vocabulary mastery has been one of the key factors to become proficient at those four skills. English learning system using gamification approach serves as one of the solutions to improve learners' motivation in learning English. The use of gamification concept integrates several elements embedded in game applications, such as point collection, achievement, ranking, which are wrapped as English learning materials. Website-based learning system can be accessed without any place and time constraint, so that learners can study English autonomously and flexibly. This type of English learning system is developed using a software development model ‘Waterfall' with some certain procedures, including needs analysis, designing, implementation, and system test. This learning system has been examined by testing unit using White box method and validation test using Black box. Based on a series of the conducted tests, it demonstrated that the functional system has been running as designed and the result of the tests showed a 100% validity level.